Studies on the Prolonged Prothrombin Time in Haemophilia BM - Elödi, Susan (Thrombosis and Haemostasis, 1973)
Prolonged prothrombin time was measured in four haemophilia B patients with the aid of bovine or rat thromboplastins, whereas normal values were obtained when human or rabbit thromboplastin was used. The anomaly can be ascribed to the decreased level of factor VII. Four carrier relatives exhibited normal prothrombin time independent of the source of thromboplastin. The prolonged prothrombin time appears to be a non-hereditary phenomenon and it may be attributed to a species- specific interaction between thromboplastin of diverse sources and human factor VII, rather than to anomalous factor IX.